2011
DOI: 10.1007/s13213-011-0270-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening fermentation parameters of the milk-clotting enzyme produced by newly isolated Bacillus amyloliquefaciens D4 from the Tibetan Plateau in China

Abstract: A bacterium producing an extracellular milkclotting enzyme was isolated from yak grazing soil in the Tianzhu Tibetan autonomous county on the Tibetan Plateau and identified as Bacillus amyloliquefaciens. We used single-factor testing to study the optimum physical conditions and nutritional parameters for production of the milk-clotting enzyme, while the temperature and pH stability of the enzyme were also studied. The optimum conditions for production of the milk-clotting enzyme were: temperature, 37°C; inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
(28 reference statements)
0
14
0
2
Order By: Relevance
“…It could be speculated that at higher rotation speeds or enhanced levels of oxygen dissolution, even higher levels of MCA might be achieved. The optimal rotation speed of 300 rpm for the BD3526 strain to produce protease was higher than those required for B. amyloliquefaciens D4 [35], M. mucedo DSM 809 [33] and B. subtilis [22] in shake-flask fermentations, which might be caused by the difference in the medium or the rotating semi-diameter of the shaker employed.…”
Section: Resultsmentioning
confidence: 99%
“…It could be speculated that at higher rotation speeds or enhanced levels of oxygen dissolution, even higher levels of MCA might be achieved. The optimal rotation speed of 300 rpm for the BD3526 strain to produce protease was higher than those required for B. amyloliquefaciens D4 [35], M. mucedo DSM 809 [33] and B. subtilis [22] in shake-flask fermentations, which might be caused by the difference in the medium or the rotating semi-diameter of the shaker employed.…”
Section: Resultsmentioning
confidence: 99%
“…1(A)]. Higher inoculation rates decreased the MCA due to limitation of nutritional supply in the growth medium (He et al, 2012). Figure 1B showed that the MCA of B. methanolicus LB-1 was the highest when the rate of filled liquid medium in the flask was at 30%.…”
Section: Resultsmentioning
confidence: 99%
“…Proper agitation of culture would facilitate MCA by letting in more air, therefore oxygen, but some other studies presented otherwise different results, that still culture would yield a higher MCA (Hashem, 2000;Narwal et al, 2017;Sun et al, 2014), which was possible due to the differences in the nature of strains. He et al (2012) indicated that the initial pH of growth medium strongly affected enzyme reaction and transport of various components across the cell membrane, thus the MCA of B. methanolicus LB-1. It was evident from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat bran, an agro-industrial residue, contains cellulose material, starch, crude protein, trace elements, and other certain ingredients, which can be used as carbon and nitrogen sources to promote the growth of microorganisms and milk-clotting enzyme production through solid-state fermentation [21,23,24,26]. However, there are few reports on the utilization of wheat bran juice for microbes to produce milk-clotting enzymes by submerged fermentation [10,13,14]. Therefore, we used this material for milkclotting enzyme production by B. amyloliquefaciens D4 under submerged fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…B. amyloliquefaciens D4, which can producing milkclotting enzyme, has been isolated from yak grazing soil in the north-eastern Tibetan Plateau [14]. The objective of the present work was to attempt to optimize the medium components with a statistical optimization strategy to increase milk-clotting enzyme production by B. amyloliquefaciens D4 using wheat bran juice.…”
Section: Introductionmentioning
confidence: 99%